PERANCANGAN DAN IMPLEMENTASI APLIKASI PENCATATAN KEGIATAN POSYANDU DENGAN PENDEKATAN AGILE - Hidayat, Syamsu; Nur Arifah, Fatimah; Silvanie, Astried; Rifiyanti, Hafizah (STMIK BINA PATRIA, 2025)
This research creates a website-based information system for recording Posyandu activities using Agile methods that support flexible development. This system is made so that cadres can more easily record data on toddlers and pregnant women and provide appropriate recommendations regarding nutritional status based on weighing results. The Black Box method is used for testing to ensure the application functions according to user needs. The test results show that this system can improve recording efficiency and support health decision making more quickly and accurately. It is recommended for further development that the system can be connected to government health services and has a notification feature to improve Posyandu services.